Interfacial stabilization of the antitumoral drug Paclitaxel in monolayers of GM1 and GD1a gangliosides - Heredia, Valeria (2015)
Molecular interactions between the anti-cancer agent Paclitaxel (Ptx), and two gangliosides with different sialic acid content, GM1 and GD1a, were investigated using the Langmuir film balance technique. Ptx showed interfacial activity reducing the air/water surface tension by 18 mN.m− 1. However, the drug was able to insert into preformed ganglioside monolayers at much higher surface pressures, indicating a preferential interaction of Ptx with GM1 and GD1a. Compression isotherms of binary mixtures of Ptx and GM1 or GD1a also indicated non-ideal mixed monolayers in which the drug became stabilized at the interface in the presence of gangliosides. Ptx reached much higher surface pressure values in the mixed monolayers than those sustained in pure Ptx, although partial desorption of the drug from the interface into the subphase was also observed at high Ptx contents. The mean molecular area of the mixtures showed condensation, mainly in the case of GD1a, whereas Ptx induced a decrease in the compressibility of monolayers when mixed with either GM1 or GD1a. Additionally, Brewster angle microscopy analysis indicated that higher amounts of Ptx are present at the mixed ganglioside/Ptx interface when compared to pure drug monolayers. Finally, GD1a micelles increased in size in the presence of Ptx, whereas GM1 micelles kept their diameter, according to Dynamic light scattering measurements, which could be explained by the different properties of ganglioside monolayers. The results obtained on ganglioside - Ptx interactions allowed interpreting the different Ptx loading capacity of GM1 and GD1a, enabling them to act as potential drug carriers.